K-Coverage Persevering Routing Technique Based on Event Occurrence Patterns for Wireless Sensor Networks. (15th May 2012) - Rafigh, Majid; Abbaspour, Maghsoud
Abstract : Wireless sensor networks (WSNs) comprising of tiny, power-constrained nodes are gaining popularity due to their potential use in a wide range of applications, including monitoring of environmental attributes, intrusion detection, and various military and civilian environments. While the sensing objectives of these environments are unique and application dependent, a common performance criteria for wireless sensor networks is prolonging network lifetime while satisfying coverage and connectivity in the deployment region. In many real-world scenarios, reoccurring spatial patterns of occurrence could be identified in the sensed event information. This paper proposes a new routing algorithm schema based on event occurrence history to secure K-Coverage of event paths and maintain the maximum degree of coverage. In the proposed method the nodes located around event path try to save their battery power by not participating in data packet forwarding to neighbor nodes. The simulation results show that the proposed method improves network lifetime by shifting the routing responsibility from sensing nodes to communication nodes, while maximizing the degree of coverage in the main path of event occurrence. As a consequence, the lifetime of main path coverage is increased dramatically as compared to previous methods.